Achieving Work Life Balance and its Impact on Job Satisfaction and Career Success: A Comparative Study - Manandhar, Sushma (PYC Nepal Journal of Management, 2016)
The paper aims to provide empirical evidence on impact of work life balance and its impact on job satisfaction and career success in the television and hospital sectors. The structured questionnaire survey of 150 personnel was taken. The study followed descriptive design to compare mean values. Correlation and regression analyses were carried on and proposed hypotheses were tested. Work life balance has shown significant positive impact on job satisfaction in the both television and hospital sectors. It also has positive impact on career success in both hospital and television sectors; but the impact is significant only in hospitals.